Young Frank, architect - Viva, Frank (<<The>> Museum of Modern Art, 2013)
"Young Frank is an architect. He lives in New York with his grandfather, Old Frank, who is also an architect, and their dog, Eddie. The two architects have very different views on what architects do for a living. This is the story of how a trip to The Museum of Modern Art in New York helps Young Frank feel older, and Old Frank feel younger-- and a little wiser."--Front jacket flap